White grubs complex (Phyllophaga spp., Anomala spp. and Cyclocephala spp.) associated to agricultural crops of the Central Valey and Dry Pacific of Costa Rica. - Abarca, Giselle (2016)
During 1990 and 1992 speciesofthe white grubs complex Phyllophaga, Anomala and Cyclocephala) were found associated to agricultural crops and to different groups of soils, in cultivated arcas of the Central Valley and Dry Pacific of CostaRica.White grubs raster and male genital, observed with the scanning electron microscope (SEM), were used to identify genera and species. Larvae and adults were identified as Phyllophaga menetriesi, P. obsoleta, P. zunilensis, P. elenans, P. vicina and P. valeriana; Cyclocephala lunulata, C. castaniella and C. sanguinicollis; and Anomala cupricollis and A. granulipyga. The distribution in agricultural crops was: P. menetriesi and P. vicina on coffee (Coffea arabica); P. menetriesi on asparagus (Asparagus officinalis); P. menetriesi, P. obsoleta, P. zunilensis, Anomala spp., Cyclocephala spp., Cyclocephala lunulata on strawberry (Fragaria anannas); P. zunilensis, P. elenans on sugar cane (Saccharum officinarum); P. valeriana on potatoe (Solanum tuberosum) and tomatoe (Lycopersicon esculentum); P. obsoleta, C. castaniella, C. sanxuinicollis and A. granulipyga on kikuyu grass (Penissetum clandestinum) P. menetriesi larvae were found in Andisols grand groups: Melanudands, Hapludands and Haplustands. P. obsoleta in the Melanudands grand group. P. vicina in Hapludands. P. valeriana in the Inceptisols grand group of Ustropepts. Anomala spp. in Hapludands and Cyclocephala spp. in Hapludands and Melanudands.